Report of the Task Force on the Fund's Technical Assistance Strategy. (Policy Papers; Policy Paper, 2011)
Fund technical assistance (TA) has undergone major changes during the last few years. On the demand side, there is increased interest in a longer-term, implementation-oriented TA, 'second generation' reforms, and in new topics. On the supply side, TA is increasingly financed by donors, and increasingly delivered through experts located in the field. These and other developments call for reassessing the Fund's TA strategy.